Rancangan Sistem Informasi Jasa Laundry - Asrori, Khasan; Kania, Raden; Maswati, Imas; Hidayanti, Nur (Teknik Informatika Fakultas Ilmu Komputer, 2023)
Nonz Eqy Laundry is a service business that is engaged in washing various types of clothes. The transaction data management system laundry that is currently running still uses the method of writing with paper media to record transactions every day. Without a system that can store laundry, data is vulnerable to lose or damage, and errors are still common in reporting. Based on these problems, it is proposed to create a web-based computerized information system that aims to assist in managing transactions and making laundry. The system is built using the Waterfall, consisting of analysis, design, implementation, and system testing stages. The design stages are carried out with application architecture design, Data Flow Diagrams (DFD), and Entity Relationship Diagrams (ERD). The implementation process uses a database and the PHP programming language with h framework Laravel. The final result achieved from this research is that the existence of laundry income reports laundry every month.